OHP-030 Efficacy of Health Literacy in the Self-Education of Diabetic Patients. (12th March 2013) - Regolo, S; Ferlito, F; Spadaro, D; Sgarlata, D; Guzzardi, S; Avola, N; Cacciaguerra, G; Italia, S
Abstract : Background: The increased prevalence of chronic diseases, including diabetes, requires a critical review of models of care and the introduction of new strategies of intervention. Health Literacy (HL) is a tool for educating patients in order to increase their understanding of medical information and thus educate them about their treatment. Diabetic patients are educated to manage the disease in accordance with the perceived needs for better compliance with drug treatment and its outcomes. Purpose: To adopt a diagnostic-therapeutic protocol shared between the diabetologist and the pharmacist, and to promote the active inclusion of people with diabetes in the course of their treatment. The secondary aim was to activate an information, monitoring and evaluation system through clinical indicators. Materials and Methods: Overall, 70 patients (32 women and 38 men) aged between 35 and 87 used the HL tool themselves and were monitored in this study. Ten patients were treated with insulin + oral hypoglycaemic agents (OHA), 53 with OHA alone and 7 with insulin alone. All patients received a sheet containing clear instructions for the proper management of the disease and treatment. The patient underwent monthly clinical monitoring, and were urged to adopt the right behaviours at home: frequent monitoring of blood glucose, a healthy and balanced diet, moderate activity and preventive screening for diabetes complications. Results: Values of blood glucose test, HbA1c, body weight and waist circumference were reduced by 42.2%, 15.2%, 6% and 3.3%, respectively. Compliance was improved in 30% of patients (screening tests carried out on time). Overall patient satisfaction was high. Conclusions: Our experience confirms that the multidisciplinary HL tool is useful for improving the communication between doctor/pharmacist and the patient. It is important to consider that the patient learning should focus on simple terms and on the knowledge of complications, in order to obtain good management of diabetes. No conflict of interest.